An Evaluation of the National Accountability Bureau (NAB) as Anti-Graft Body in the Political Perspective of Accountability in Pakistan. (2nd January 2023) - Shah, Syed Fakharuddin; Abbas, Zafar; Qayyum, Abdul
Abstract: The accountability mechanism in Pakistan is conducted through its different facets, and one of them is legal and institutional accountability. General Musharraf's regime enacted the National Accountability Ordinance in 1999. Consequently, the National Accountability Bureau (NAB) was formed as an institutional anti-graft body. The existing literature focuses on the role of the NAB as working under the National Accountability Ordinance. However, no focus has been paid to the operation of the NAB as a legal institution within the political dimensions of accountability in Pakistan. This research article is the first in this direction to evaluate the role of the NAB in the political perspective of accountability in Pakistan. The authors conclude that the ruling elites have failed to set the political scene for the successful working of the NAB, which has caused it to have potential pitfalls that outweigh its benefits by far.